Flour made from cacao-soybean tempeh fermented using soybean tempeh inoculum - WAHJUDI, Mariana; TJAHYADI, Audrey Layana; ERAWATI, Christina Mumpuni; SUKWEENADHI, Johan (Food Science and Technology, 2023)
Raw cacao beans are non-premium cacao without cacao pulp fermentation. This raw bean still contains enough protein and polyphenol contents for functional food. In this study, cacao bean was used to substitute soybeans in tempeh fermentation. The soybean-cacao tempeh, called tekao tempeh, was then processed to make tekao flour. The aim of this research was to evaluate the characteristics of the flour made from soybean:cacao tempeh. The tekao flour was made from tempeh with a soybean:cacao proportion of 70:30. The tekao flour had an antioxidant activity of 48.1% and a soluble protein content of 444.7 mg.L-1. The water- and oil-holding capacities of tekao flour were 240.4% and 107.2%, respectively. The bulk density, angle of repose, and particle size were 0.427 mg.L-1, 44.9º, and 546 mm, respectively. The water content and water activity were 7.3% and 0.55% w/w, respectively. Based on the flour characteristics, tekao flour made from 70:30 of soybean:cacao bean tempeh has the potential to be functional food considering its antioxidant properties and other characteristics.